2016
DOI: 10.3389/fpsyg.2016.01313
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the Discriminatory Work Environment as Stressor: The Protective Role of Job Satisfaction on Health

Abstract: Discrimination is a complex phenomenon with adverse consequences at personal and organizational levels. Past studies have demonstrated that workers who are victims of discrimination might show less job satisfaction, less organizational commitment and worse levels of health and productivity. Although most research has focused on the effects of discrimination on victims, less is known about the extent to which discrimination produces consequences on workers who perceive the existence of a discriminatory work env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 58 publications
3
31
0
3
Order By: Relevance
“…In line with this study, Di Marco and colleagues reiterated the role of satisfaction as a mediator in analyzing the consequences of the perception of a discriminatory work environment on health and psychological well-being of employees [15]. The perception of a discriminatory work environment has negative effects on the well-being and health of employees; this study underlines the need for Human Resource Managers to intervene to reduce explicit prejudices in order to create a healthy environment that is free of discrimination, and the importance of promoting job satisfaction to preserve personal well-being and better face potential negative effects.…”
Section: Introductionmentioning
confidence: 70%
“…In line with this study, Di Marco and colleagues reiterated the role of satisfaction as a mediator in analyzing the consequences of the perception of a discriminatory work environment on health and psychological well-being of employees [15]. The perception of a discriminatory work environment has negative effects on the well-being and health of employees; this study underlines the need for Human Resource Managers to intervene to reduce explicit prejudices in order to create a healthy environment that is free of discrimination, and the importance of promoting job satisfaction to preserve personal well-being and better face potential negative effects.…”
Section: Introductionmentioning
confidence: 70%
“…Additionally, this construct has demonstrated an impact on health desirable variables such as mental health, physical health, and the combination of both [25]. Assessing deeper the possible impact of this variable on the organizational field, recent researchers have found that job satisfaction is significantly correlated to self-evaluations, organizational commitment, job burnout [26], and job performance [27], and also on the modulating effect exerted by high job satisfaction in relation to the perception of a discriminatory job context and the negative impact on workers' health [28]. Finally, job satisfaction has been related to emotional intelligence, an important variable that has been widely researched in the organizational field showing relations with integrative conflict management styles [29].…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Furthermore, when individuals feel they are mistreated because of their group membership, they often feel alienated and angry, which can result in negative work-related behaviours. Empirical evidence shows that perceiving discrimination is a stressor which reduces physical and psychological health; reduce self-esteem, decreases job satisfaction, and increases job tension [28][29]. Research with men has shown that they do experience many of the same negative personal and occupational pressures associated with being a token that women experience in male-dominated occupations [30].…”
Section: Gender Role Conflict and Perceived Gender Discriminationmentioning
confidence: 99%